PENGARUH UKURAN KAP, AUDIT TENURE, AUDIT FEE, UKURAN PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018-2022) - Hanna Vanessa; Erika Astriani Aprilia (PT. Jurnal Center Indonesia Publisher, 2024)
Abstract This research aims to determine the effect of company size, audit tenure, audit fees, company size and financial performance on audit quality. The method used is associative with a quantitative approach. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (BEI) for the period 2018 - 2022. Samples were collected using the purposive sampling method. The amount of data observed was 92 companies, resulting in 46 companies or 230 observation data. Data were processed using the Eviews 10 Statistical Program to test hypotheses using logistic regression analysis. The results reveal that KAP size, audit tenure, audit fee, company size, and financial performance simultaneously influence audit quality, then the results of the t statistical test show that audit fees and company size have a positive effect on audit quality, but KAP size, audit tenure and financial performance have no effect on audit quality.